PENGARUH PERSEPSI HARGA, ATMOSFER TEMPAT, DAN VARIASI MENU TERHADAP LOYALITAS PELANGGAN GISOE COFFEE SURABAYA - Kevin Cristoval Clarence Clarence; Dr. Romauli Nainggolan (Jurnal Performa)
Abstract: Coffee industry can be considered as extensive industry. Recently the industry has undergone several developments and changes due to various phenomenon that occur. This thing also occurs at coffee industry for coffee to go. With the existing competition, of course each coffee shop has different characteristics of loyal customers. The purpose of this research is to be able to find out the influence of Price Perception, Store Atmosphere, and Menu Variation on Customer Loyalty of Gisoe Coffee Surabaya. The research that is done is quantitative research by using Likert scale questionnaire distribution method with the scale of 1 to 5. In this research, the population that is analyzed is active customers of Gisoe Coffee Surabaya that domicile in Surabaya. The questionnaire in this research is distributed to 160 respondents. In data analysis process, this research uses SPSS version 27. The result that is found is Price Perception variable influences significant positive on Customer Loyalty. Another result that is found is Store Atmosphere has significant positive influence on Customer Loyalty. The final finding that is obtained is Menu Variation has significant positive influence on Customer Loyalty. Thus, it can be stated that Price Perception, Store Atmosphere, and Menu Variation have influence significantly and all hypotheses are accepted